(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
Cortazar’s writings from the 1960s show a preoccupation with form: new semiotic events as a work in progress. His miscellaneous books composed of minor texts – “minor” because of their brevity – can pass for notebooks, being a window into Cortazar’s creative process. Working with such unstable forms requires a critical reader, even though even professional readers can experience the same perplexity. Cortázar´s innovation comes from using what’s been cast aside. The perplexity of the texts comes from the work in progress effect of their object rather than of the writing itself. The object is seen or thought from a place that barely puts an end to the process of writing in order to leave it in a stable place. Through a series of close readings from The Final Round and Around the Day in Eighty Worlds, we will look into the effect of perplexity that defines their creative process.